Administration of Drugs to Treat COVID-19 in Uzbekistan - Umid Sanjarovich Akbarov; Tamara Uktamovna Aripova; Adolat Abdurahimovna Ismailova; A'zam Akbar Ug'li Rakhimjonov; Larisa Viktorovna Sher; Tatyana Aleksandrovna Petrova; Muxlisa Saidakbarhojaevna Kasimova; Dildora Sobirjon Qizi Karimova; Ramazan Joldasbaevich Rozumbetov (Shiraz University of Medical Sciences, 2023)
The COVID-19 pandemic has become a big challenge for the health systems of all countries. Since there were no reliable data on the efficacy of various drugs for COVID-19 in the early months of the pandemic, medical staff had to rely on constantly changing temporary recommendations and their experience in managing patients with COVID-19. In this regard, it is important to study the actions of medical personnel in a pandemic. In this study, we investigated the administration of drugs to treat COVID-19 in Uzbekistan. We demonstrated that physicians were swiftly adapting to new therapy recommendations; however, some drugs were not used appropriately, e.g., antibiotics and dexamethasone.